2018
DOI: 10.1111/plb.12840
|View full text |Cite
|
Sign up to set email alerts
|

Physcomitrella patens Reute mCherry as a tool for efficient crossing within and between ecotypes

Abstract: Physcomitrella patens is a monoecious moss that is predominantly selfing in the wild. Laboratory crossing techniques have been established and crosses between the sequenced Gransden ecotype and the genetically divergent Villersexel ecotype were used for genetic mapping. The recently introduced ecotype Reute has a high fertility rate and is genetically more closely related to the Gransden ecotype than the Villersexel ecotype. Reute sexual reproduction phenology is similar to Gransden, which should allow success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 30 publications
2
43
0
Order By: Relevance
“…The ecotype Reute (Re) was shown to develop a significantly higher number of sporophytes per gametophore in comparison to the broadly used ecotype Gransden (Gd, (Hiss et al 2017)). To determine whether the reduced fertility of Gd is based on the female or male reproductive apparatus, crossing analyses between Gd and Re were performed, using the fluorescent marker strain Re-mCherry (Perroud et al 2011, Perroud et al 2019. Re developed on average 100% sporophytes per gametophore, of which 0.79% were crosses ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ecotype Reute (Re) was shown to develop a significantly higher number of sporophytes per gametophore in comparison to the broadly used ecotype Gransden (Gd, (Hiss et al 2017)). To determine whether the reduced fertility of Gd is based on the female or male reproductive apparatus, crossing analyses between Gd and Re were performed, using the fluorescent marker strain Re-mCherry (Perroud et al 2011, Perroud et al 2019. Re developed on average 100% sporophytes per gametophore, of which 0.79% were crosses ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…When no fertilization takes place, P. patens is known to continue gametangiogenesis, leading to the accumulation of multiple archegonia per gametophore (Landberg et al 2013, Sanchez-Vera et al 2017. Under crossing conditions using the male fertile Re-mCherry line (Perroud et al 2019) a close to normal amount of sporophytes (94%) could be observed, with 100% of them being crosses (Fig. 4A, light and dark green), suggesting a defect in the male reproductive apparatus.…”
Section: Analysis Of Differentially Expressed Genes Between Gd and Rementioning
confidence: 98%
See 2 more Smart Citations
“…This LOX readily oxidises polyunsaturated fatty acids even in vitro, making it a valuable pioneer enzyme for the study of algal LOXs in general. Similarly, in their study of ecotypes of the moss Physcomitrella, Perroud et al (2019) establish the highly fertile ecotype Reute as a new background for transformation and outcrossing to other ecotypes. They also created a Reute strain expressing the red fluorescent protein mCherry that allows easy detection of offspring from crosses between divergent ecotypes.…”
mentioning
confidence: 99%